A novel conceptual framework investigating the relationship between roadside advertising and road safety: The driver behaviour and roadside advertising conceptual framework. (February 2022) - Hinton, Jane; Watson, Barry; Oviedo-Trespalacios, Oscar
Highlights: A conceptual framework is proposed to explore the phenomena of roadside advertising, reflecting the complex and dynamic nature of its impacts on driver behaviour. The DBRA framework delineates three time-related exposure phases to roadside advertising signs – pre-exposure, exposure and post-exposure. "Extended engagement" is a proposed new term to describe situations where a driver's attention to a roadside advertising sign is prolonged, even after the sign has been passed. The DBRA framework provides a common point of reference to facilitate a consistent research agenda relating to roadside advertising. Abstract: This paper proposes a conceptual framework to understand the relationship between roadside advertising signs, driver behaviour, and road safety outcomes. Roadside advertising signs are external distractions that may take a driver's attention away from safety-critical driving tasks, potentially increasing crash risk through driver distraction and inattention. Although studies report safety concerns, as a whole, the body of research in the field is inconclusive with inconsistent quality, making it difficult to draw firm conclusions. Definitive links between roadside advertising and road trauma are not yet evident, which has major consequences for road regulators' capacity to develop evidence-based policy to safely administer public roads. However, a lack of consistent evidence does not indicate an absence of risk but underscores its complexity. To address this problem, the Driver Behaviour and Roadside Advertising Conceptual Framework (DBRA framework) was developed to strategically investigate and conceptualise the phenomena of roadside advertising. A new term – "extended engagement" – has also been proposed to account for situations of prolonged attentional engagement with a roadside advertising sign. Further, it is posited that important variations in driving performance may be associated with a driver's extended engagement with a roadside advertising sign. Built on extant theories of driver behaviour and empirical research, the DBRA framework is designed to be a robust tool that encourages a common agenda for future roadside advertising research.